A study on the effects of chilling period on sperm quality of Sannan and Jamunapari goats. - Eswaramohan, T.; Nilani, K.; Sureka, P.; Mahadhevan, P.; Balasubramaniam, K. (Islamic Azad University, 2014)
The objective of the present study was to examine the effects of chilling period on semen quality of Sannan and Jamunapari. Semen of goat breeds were collected with artificial vagina and chilled at 5-9°C. Volume, colour and pH were determined on fresh semen. After dilution, microscopic examination was performed for the progressive motility and sperm viability. Diluted semen of both breed was compared by microscopic examination from day 0 to 3 during chilling. Hemocytometer was loaded with 10 µL of semen to evaluate the sperm count. Eosin stain (1%) was used to assess the viable sperm. Although viability and sperm velocity of both goat breed decreased (P<0.05) in a time dependent manner during chilling, the viability between the Sannan and Jamunapari did not differ significantly. However there was a significant difference for means of sperm velocity (P<0.05). Progressive motility and viability decreased gradually during chilling at 5-9°C. In order to obtain higher successful rate of insemination, chilled goat semen should be supplied to the farmers within a day. Up to 10,525,429 more results found for "???"